MANAJEMEN PESERTA DIDIK DALAM MENINGKATKAN PRESTASI BELAJAR SISWA DI SATUAN PENDIDIKAN - Nurhasanah Belianti; Sholeh Hidayat; Fadlullah Fadlullah (STKIP Pesisir Selatan, 2026)
Student management is an important component in the implementation of education that plays a role in improving the quality of learning services and student achievement. This study aims to analyze the implementation of student management in improving student learning achievement in educational institutions and to identify its supporting and inhibiting factors. The study employed a library research method with a descriptive qualitative approach. Data were obtained from various literature sources, including accredited scientific journals, books, articles, and relevant documents related to student management and learning achievement. Data collection techniques were carried out through reading, recording, classifying, and analyzing relevant references. The results indicate that student management implemented through the functions of planning, organizing, actuating, and controlling is able to create a conducive learning environment, improve discipline, increase learning motivation, and develop students’ academic and non-academic potential. The success of student management is also influenced by collaboration among principals, teachers, parents, and adequate educational facilities and infrastructure. Therefore, effective student management becomes an important factor in improving the quality of education and student achievement in schools.